IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR IPAS MATERI PERUBAHAN WUJUD BENDA KELAS IV SD NEGERI 112 PALEMBANG - Dini Anggraeni; Siti Dewi Maharani; Firdaus (STKIP Subang, 2024)
The aim of this research is to improve science learning outcomes related to changes in the shape of objects using a problem-based learning model. This type of qualitative research uses a classroom action research method which includes four stages, namely planning, implementation, observation and reflection. The subjects of this research were 28 class IV students at SDN 112 Palembang. Data collection methods in this research are experimentation, observation and document research. The data analysis method used is analyzing experimental results and observation results. Based on the research results, it can be concluded that the problem-based learning (PBL) model can improve the science and science learning outcomes of class IV students at SD Negeri 112 Palembang based on scientific information about changes in the shape of objects. The increase in learning outcomes shows that learning outcomes using the PBL learning model bring better student learning outcomes. In this study, learning outcomes were obtained which experienced an increase in learning outcomes, where the results from cycle I obtained a total score of 1228, while the average score was 43.8, with a percentage score of 10.7%, achieving an increase in the results of the posttest cycle I with a total score of 2287 which has an average score of 81.7 and a completion percentage of 53.5%. Meanwhile, in cycle II there was an increase in the posttest with a completion percentage of 100% and a score of 2658 which had an average score of 94.9.